Numerical Investigation of the Sediment Hyperpycnal Flow in the Yellow River Estuary - Zhiguo He; Baoxin Xu; Samuel Ukpong Okon; Li Li (Journal of Marine Science and Engineering, 2022)
Sediment hyperpycnal flow is one of the most important processes for mass transport, which is essential to coastal morphodynamics. Herein, we studied the generation and maintenance of the sediment hyperpycnal flow in the Yellow River Estuary (YRE) using a three-dimensional finite volume coastal ocean model (FVCOM). The model considered the effect of sediment-laden water on density stratification, and was validated by field hydrodynamic and sediment data. Numerical results revealed that the hyperpycnal flow shows periodic characteristics with tidal cycles where the flow is weakened during flood tides and enhanced during ebb tides. A high suspended sediment concentration (SSC) of about 30–40 kg/m3 constitutes an important factor in the formation of hyperpycnal flows. High river discharge with high SSC is essential for maintaining the hyperpycnal flow in the YRE. The Simpson potential energy theory was applied to study the processes of estuarine circulation, tidal straining, and tidal stirring in the YRE. The tidal straining is the main control factor of the periodic stratification-mixing process of hyperpycnal flows in the YRE. Along the axis of the river mouth, the momentum balance is mainly dominated by the pressure gradient and advection.